PENERAPAN TEKNOLOGI DI AIK DESIMINATIF: MENGOPTILMAKAN PROSES PENYEBARAN NILAI KEAGAMAAN - La Sahara; Mukayat Al Amin (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
The development of digital technology presents both challenges and opportunities in the dissemination of Al-Islam and Kemuhammadiyahan (AIK) values. This study aims to analyze the application of digital technology and to formulate an optimization model for disseminating AIK values that aligns with the characteristics of digital society. A qualitative case study approach was employed, with data collected through in-depth interviews, participant observation, and documentation from institutions actively utilizing digital platforms. The findings indicate that effective dissemination of AIK values is achieved through an integrated multi-platform digital ecosystem rather than reliance on a single medium. Social media functions to expand outreach, application-based platforms facilitate personalized interaction, and long-form video channels support in-depth learning. The effectiveness of this strategy is strengthened by a hybrid team model that integrates religious expertise and digital literacy in content management and audience engagement. The study concludes that optimizing the dissemination of AIK values requires the integration of technology, layered content strategies, collaborative human resources, and interactive community-based approaches. These findings contribute a conceptual framework that may serve as a reference for educational and religious institutions in developing sustainable digital-based religious value dissemination. Perkembangan teknologi digital menghadirkan tantangan sekaligus peluang dalam diseminasi nilai-nilai Al-Islam dan Kemuhammadiyahan (AIK). Penelitian ini bertujuan menganalisis penerapan teknologi digital serta merumuskan model optimalisasi diseminasi nilai AIK yang sesuai dengan karakteristik masyarakat digital. Penelitian menggunakan pendekatan kualitatif studi kasus dengan pengumpulan data melalui wawancara mendalam, observasi partisipan, dan studi dokumentasi pada institusi yang aktif memanfaatkan platform digital. Hasil penelitian menunjukkan bahwa diseminasi nilai AIK yang optimal dicapai melalui ekosistem digital multi-platform yang terintegrasi, bukan melalui satu media tunggal. Media sosial berperan dalam memperluas jangkauan, platform aplikasi mendukung interaksi personal, dan kanal video berdurasi panjang berfungsi untuk pendalaman materi. Keberhasilan strategi ini diperkuat oleh model tim hibrida yang mengombinasikan kompetensi keagamaan dan literasi digital dalam pengelolaan konten dan interaksi audiens. Penelitian ini menyimpulkan bahwa optimalisasi diseminasi nilai AIK memerlukan integrasi teknologi, strategi konten berlapis, kolaborasi sumber daya manusia, serta pendekatan komunitas yang interaktif. Temuan ini memberikan kontribusi konseptual berupa kerangka strategis yang dapat dijadikan acuan bagi institusi pendidikan dan dakwah dalam mengembangkan diseminasi nilai keagamaan berbasis digital secara berkelanjutan.